Screening Nickel‐Doped Mo2C Nanorod Arrays for Ultrastable and Efficient Hydrogen Evolution over a Wide pH Range. Issue 1 (20th January 2023) - Yuan, Meichen; Nie, Zhongxiang; Tang, Zeming; Lai, Qingxue; Liang, Yanyu
Abstract: Green hydrogen, using sustainable energy to decompose water to produce hydrogen, is regarded as the ideal and effective connection to convert electricity into chemical energy. Herein, well designed Ni‐doped Mo2 C nanorod electrodes self‐supported on three types of substrates (Ni foam, Cu foam and stainless steel wire mesh) with outstanding gas resistance and prominent corrosion resistance were assembled together to build up a wide pH applicable electrode for Hydrogen Evolution. In particular, Ni‐doped Mo2 C nanorod arrays on stainless steel wire mesh donated as Ni−Mo2 C@SSW exhibited remarkable electrocatalytic properties towards hydrogen evolution reaction with superior overpotentials both in 1 M KOH and 0.5 M H2 SO4 (102 mV and 106 mV at the current density of 10 mA cm −2 ) and incomparable continuous durability. This work provides the possibility for the realization of low cost, high activity and ultra‐stable durability HER electrocatalysts in practical industrial application. Abstract : Ni‐doped Mo2 C nanorods with high catalytic activity, arrays with outstanding gas resistance and self‐supporting substrates with prominent corrosion resistance were assembled together to fabricate wide pH applicable electrode by solvothermal method and chemical vapor deposition technology. The obtained composite electrodes exhibited remarkable catalytic properties towards hydrogen evolution.